Transformasi Desain Pembelajaran Kolaboratif dalam Mendukung Pembelajaran Aktif - Fauza Okta Ramadan; Syarif Rusdan; Gusmaneli Gusmaneli (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Collaborative learning is an effective approach in enhancing student learning outcomes, particularly in developing cognitive, social, and emotional skills. Through interactions among students within groups, this learning model allows them to share knowledge, discuss, and solve problems together, leading to a deeper understanding of the material. Furthermore, collaborative learning fosters critical thinking, creativity, and communication skills, which are essential for addressing the challenges of the 21st century. Despite its numerous benefits, the implementation of collaborative learning faces several challenges, such as unequal participation among group members and the need for effective group dynamics management. Therefore, the role of the teacher is crucial in managing the collaboration process to ensure optimal contribution from each student. Overall, collaborative learning has a positive impact on improving student learning outcomes and supports the development of skills relevant to future life.